Industrial-scale Investigations on Combustion Characteristics and NOx Emissions of a 300-MWe Down-fired Boiler: Bituminous Coal Combustion and Coal Varieties Comparison. Issue 15 (18th November 2022) - Zhang, Xin; Chen, Zhichao; Li, Liankai; Zeng, Lingyan; Li, Zhengqi
ABSTRACT: Number of down-fired boilers burning bituminous coal or anthracite blended with bituminous coal has exceeded 10% of the total down-fired boilers in China. However, lacking of the industrial-scale research on the performance of down-fired boiler burning bituminous coal or blended coal, which limits the actual operation adjustment. Industrial-scale experiments on a 300-MWe down-fired boiler fueled with bituminous coal and blended coal were performed, which boiler was originally designed to burn low-volatile coal. Without the over-fire air, air-staging combustion can still be realized when the down-fired boiler burning bituminous coal. The combustion performance in the down-fired boiler under different coal varieties was compared. Compared with the anthracite case, flue gas temperature is higher, coal flame fullness is greater, O2 consumption occurs faster and NO x concentration is lower in the primary combustion zone when burning bituminous coal. Strong reducing atmosphere is formed in the primary combustion zone. The NO x emissions are low at a level of 410 mg/m 3 at 6% O2 at furnace exit and boiler thermal efficiency reaches 92.590% when burning bituminous coal. The NO x emissions cannot be further reduced by burning blended coal. In addition, the boiler thermal efficiency reduced by 1.108%. Without the over-fire air, compared with burning anthracite or lean coal, the NO x emissions and carbon in fly ash significant reduction by 70% and 90%, respectively, and the boiler thermal efficiency increased when burning bituminous coal. GRAPHICAL ABSTRACT: uf0001